Origins and Distinctions of the "World Music" and "World Beat" Designations - Klump, Brad (Canadian University Music Review / Revue de musique des universités canadiennes, 1999)
This article traces the origins and uses of the musical classifications "world music" and "world beat." The term "world beat" was first used by the musician and DJ Dan Del Santo in 1983 for his syncretic hybrids of American R&B, Afrobeat, and Latin popular styles. In contrast, the term "world music" was coined independently by at least three different groups: European jazz critics (ca. 1963), American ethnomusicologists (1965), and British record companies (1987). Applications range from the musical fusions between jazz and non-Western musics to a marketing category used to sell almost any music outside the Western mainstream.